2016
DOI: 10.1007/s12325-016-0459-6
|View full text |Cite|
|
Sign up to set email alerts
|

Chronic Obstructive Pulmonary Disease Individualized Therapy: Tailored Approach to Symptom Management

Abstract: Chronic obstructive pulmonary disease (COPD) is associated with high morbidity and mortality. COPD is typified by persistent, progressive airflow limitation and a range of respiratory and systemic symptoms such as breathlessness, coughing, wheezing, depression, anxiety, general fatigue, and sleeping difficulties. Despite receiving treatment for COPD, many patients suffer from regular symptoms that affect their daily lives and lead to increased morbidity. These symptoms vary in severity, frequency, and type, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 67 publications
0
30
0
1
Order By: Relevance
“…Symptoms and exacerbation history were defined in accordance with the revised GOLD recommendations, which suggest that either CAT or mMRC can be used to assess the impact of symptoms [13]. However, there are data suggesting that CAT and mMRC might not be equivalent [10,11], and we therefore performed analyses for both.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms and exacerbation history were defined in accordance with the revised GOLD recommendations, which suggest that either CAT or mMRC can be used to assess the impact of symptoms [13]. However, there are data suggesting that CAT and mMRC might not be equivalent [10,11], and we therefore performed analyses for both.…”
Section: Discussionmentioning
confidence: 99%
“…However, the data reviewed herein provide information to identify patient groups that may benefit from ICS use (Figure 2). Concerns with ICS use are related to the safety considerations described in the previous section and the potential risks associated with withdrawal of ICS therapy 45,74,78. Long-term adverse events described in some studies are complicated by concomitant oral CS use and confounding disease severity, as well as comorbidities.…”
Section: Role Of Icss In Current Copd Treatmentmentioning
confidence: 99%
“…21 Our results on the prevalence of daytime/nighttime symptoms, breathlessness being the most common symptom, prevalence of sleep impairment, and more than half of patients being dissatisfied with their current medications' ability to control symptoms were in general agreement with previous studies. 4,17 Previous studies have reported that concordance of symptom burden and impact on HRQOL reports from physicians and patients are greater for patients with more severe COPD compared with those with milder disease. 21 In our study, there was reasonable concordance between physician-and patient-reported responses describing symptom burden, suggesting that physician-patient communication is not a barrier to improving care for patients with more severe disease, although it may be a factor for those with milder disease.…”
Section: Discussionmentioning
confidence: 99%